Acute Pancreatitis Masquerading as Inferior Wall Myocardial Infarction: A Review - Elliot S. Yu (Case Reports in Gastroenterology, 2019)
A rare presentation of acute pancreatitis is with electrocardiographic (ECG) changes that mimic myocardial ischemia. We present a report of a patient that presented with hemodynamic instability and new ECG changes of ST segment elevations in contiguous leads II, III, and aVF mimicking an inferior wall myocardial infarction. Emergent coronary angiography showed no significant coronary obstruction, but it was followed by a left-sided hemiplegia with radiographic evidence of diffuse embolic stroke. The patient was later found to have an underlying diagnosis of pancreatitis. Additional history that later became available indicated a history of severe acute pancreatitis treated elsewhere a few months prior to the current admission. We present the first comprehensive review of the literature comprising 36 total cases with pancreatitis masquerading as acute myocardial infarction, with inferior wall STEMI pattern being the most frequent. We present this case to highlight the diagnostic dilemma posed by this masquerade of a high acuity myocardial infarction and to highlight alternative diagnoses to be considered in such clinical circumstances.